Endophytic fungi from Passiflora incarnata: an antioxidant compound source - da Silva, Matheus Henrique Reis [UNESP] (2020)
Endophytes are considered one of the most important microbial resources for obtaining biomolecules of therapeutic use. Passiflora incarnata, widely employed by the pharmaceutical industry, shows therapeutic effects on anxiety, nervousness, constipation, dyspepsia and insomnia based on their antioxidant compounds. In this study, from 315 endophytic fungi isolated from P. incarnata leaves, 60 were selected to determinate presence of chemical constituents related with antioxidant activity, based on their production of soluble pigments. The promising fungi were evaluated specifically on their potential to produce phenolic compounds, flavonoids and for antioxidant activity. Five isolates significantly produced flavonoids and phenolic compounds in the ethyl acetate and n-Butanol extracts, also saponins and high antioxidant activity against the DPPH (2.2-diphenyl-1-picrylhydrazyl) free radical. A strain of Aspergillus nidulans var. dentatus (former Emericella dentata) was able to produce tannins as well; its butanolic extract was very similar than the BHT (butylated hydroxytoluene) (94.3% × 94.32%) and Rutin (95.8%) reference substances in the DPPH radical scavenging. Similarly, a Chaetomium strain exhibited 93.6% and 94.7% of antioxidant activity in their ethyl acetate and butanolic fractions, respectively. The chromatographic analysis of the ethyl acetate fraction from the Aspergillus strain revealed the production of orcinol (3.19%). Four-methoxymethylphenol (4.79%), sorbicillin (33.59%) and ergosterol (23.08%) was produced by Trichoderma longibrachiatum and isopropenyl-1,4-dimethyl-1,2,3,3a,4,5,6,7-octahydroazulene were found in two Fusarium oxysporum strains. The phytochemical screening showed that all analyzed fungi were able to produce a kind of secondary metabolite (phenols, flavonoids, tannins and/or saponins). The study shows a great underexplored potential for industrial application of P. incarnata endophytes.